Assessment of refractory gold-bearing ores based of interpretation of thermal analysis data - Aleksandrova Tatyana N.; Heide Gerhard; Afanasova Anastasiya V. (Федеральное государственное бюджетное образовательное учреждение высшего образования «Санкт-Петербургский горный университет», 2019)
The article presents the results of a study on the possibility to assess refractory gold-bearing ores using thermal analysis data. It studies the flotation concentrates obtained during the enrichment of double refractory sulfide goldbearing ores. This type of ore is complicated by the fine impregnation of gold in sulphide minerals and the presence of sorption-active scattered carbonaceous matter, which is in close association with sulphides. The results of thermogravimetric and mass spectrometric studies of refractory gold-bearing ores are presented. The obtained fragments for kerogen CH3 (m/z = 15), C2H3 (m/z = 29) and C3H) (m/z = 43) indicate the presence of various types of carbonaceous matter in the studied samples. It is justified that the degree of sorption activity of carbonaceous matter depends on the presence of kerogen and bitumen in the ore. High sorption activity of scattered carbonaceous material significantly affects the processing technology of ores and concentrates, both flotation and pyroand hydrometallurgical methods. Thermogravimetric and mass spectroscopic analyzes can be used to determine the degree of preg-robbing of refractory gold-bearing ores. The obtained results predetermine the direction of creating new methods and technologies in the field of decarburization of refractory gold-bearing ores in the integrated development of solid minerals in the mining regions of Russia.
Keywords: black slates; pyrolysis; kerogen; bitumen; gold ore; sulphides; high sorption activity; carbon matter